The Impact of Audit Committee Characteristics on Audit Quality: Evidence from Saudi Arabia - Boshnak, Helmi A. (International Review of Management and Marketing, 2021)
This study examines the impact of audit committee (AC) characteristics on audit quality in the Saudi listed firms. In addition, this study is also evaluating the Saudi CG Code amended in 2017. The data for the study is obtained from secondary (annual reports) data. The sample firms are 210 firms listed on the Saudi Stock Exchange (Tadawul) over the period of 2017-2019. The audit firm type is used as a proxy for quality in this study. Multiple regression analysis is used to assess the relationship between AC characteristics and audit quality. The regression models show that firms with AC educational background in accounting and finance, and larger firms with higher state and institutional ownership are more likely to engage a big four audit firm, in so doing signalling greater audit quality. The results support agency and institutional theories concerning audit quality. In contrast, firms with more experts on the AC and higher leverage are more likely to select non-big four auditing firms which require lower audit fees. However, the size, number of meetings, and degree of independence of the AC do not significantly affect the level of audit quality. In addition, a combined AC effectiveness score is found to have a negative though insignificant impact on audit quality, contradicting governance regulation and theory expectations that effective ACs should improve audit quality. The results of this study present some key implications for CG regulators and other stakeholders. CG regulators should understand that the simple presence of an AC that meets baseline CG regulatory requirements does not automatically ensure its efficacy or improve auditing process quality. Therefore, boards and shareholders must continue to monitor and review AC decisions, particularly where they relate to auditor engagement, even where committees are, prima facie, deemed effective. The study contributes to the existing body of literature on the role of the audit committee in improving audit quality by addressing the paucity of evidence for emerging economies, and the case of Saudi Arabia in particular. The findings should prove useful for regulators and policy makers, academic researchers, accountants, financial experts, and audit practitioners in the Middle East and wider Arab region, particularly for those countries currently reviewing and setting guidelines for effective audit committees. Moreover, the findings should emphasise the importance of the concept of audit quality and its drivers in a Saudi Arabian corporate setting. Keywords: Audit Quality, Audit Committee Characteristics, Audit Committee Effectiveness, Corporate Governance, Corporate Governance Code, Saudi Arabia. JEL Classifications: G3, M4 DOI: https://doi.org/10.32479/irmm.11437